Index to Proceedings of the Security Council: Seventy-third Year, 2018 - United Nations (United Nations, 2019)
The Index to Proceedings of the Security Council is a bibliographic guide to the proceedings and documentation of the Security Council. This issue covers the seventy-third year of the Council including its commissions, committees and ad hoc committees. The Index is divided in two parts comprising the Subject Index and Index to Speeches. The Index is prepared by the UN Dag Hammarskjöld Library as one of the products of the United Nations Bibliographic Information System.